Lactose-modified DNA tile nanostructures as drug carriers. (13th September 2016) - Akkus Sut, Pinar; Tunc, Cansu Umran; Culha, Mustafa
Abstract: Background: DNA hybridization allows the preparation of nanoscale DNA structures with desired shape and size. DNA structures using simple base pairing can be used for the delivery of drug molecules into the cells. Since DNA carries multiple negative charges, their cellular uptake efficiency is low. Thus, the modification of the DNA structures with molecules that may enhance the cellular internalization may be an option. Objective: The objective of this study is to construct DNA-based nanocarrier system and to investigate the cellular uptake of DNA tile with/without lactose modification. Methods: Doxorubicin was intercalated to DNA tile and cellular uptake of drug-loaded DNA-based carrier with/without lactose modification was investigated in vitro . HeLa, BT-474, and MDA-MB-231 cancer cells were used for cellular uptake studies and cytotoxicity assays. Using fluorescence spectroscopy, flow cytometry, and confocal microscopy, cellular uptake behavior of DNA tile was investigated. The cytotoxicity of DNA tile structures was determined with WST-1 assay. Results: The results show that modification with lactose effectively increases the intracellular uptake of doxorubicin loaded DNA tile structure by cancer cells compared with the unmodified DNA tile. Conclusion: The findings of this study suggest that DNA-based nanostructures modified with carbohydrates can be used as suitable multifunctional nanocarriers with simple chemical modifications.